Twenty-five years of research on the effects of exercise training in breast cancer survivors: A systematic review of the literature - Battaglini, Claudio L (Baishideng Publishing Group Co., Limited, 2014)
AIM: To investigate the role of exercise training the past 25 years on major physiological-psychological outcomes studied thus far in this patient population. METHODS: PubMed, MedlinePlus, the Cochrane Library, Web of Science, SportDiscus, Embase, Scorpus, and Google Scholar were searched from September to November 2013 to identify exercise training studies that used objective measurements of fitness and/or patient reported outcomes assessed pre and post-exercise training with statistical analyses performed in at least one of the following outcome measurements: Cardiorespiratory function, body composition, muscular strength, fatigue, depression, and overall quality of life. Five reviewers independently identified the studies that met the criteria for the review and discrepancies were resolved by consensus among all authors. RESULTS: Fifty-one studies were included in this review with 5 from the period between 1989-1999, 11 from 2000-2006, and 35 from 2007-2013. The evolution of study designs changed from aerobic only exercise training interventions (1989-1999), to a combination of aerobic and resistance training (2000-2006), to studies including an arm of resistance training or examining the effects of resistance training as the main mode of exercise (2007-2013). Overall, the benefits of exercise showed improvements in cardiorespiratory function, body composition, strength, and patient reported outcomes including fatigue, depression, and quality of life. CONCLUSION: Exercise training appears to be safe for most breast cancer patients and improvements in physiological, psychological, and functional parameters can be attained with regular participation in moderate intensity exercise.